UJI KESUBURAN TANAH BERDASARKAN KUALITAS LAHAN SAWAH DI DESA TAUGI KECAMATAN MASAMA - Sule, Dhea A.S; Yatim, Hertasning; Yatim, Herwin; Ahmad, Sutarmin H. Di (Fakultas Pertanian Universitas Tompotika Luwuk, 2024)
Taugi Village, Masama District is one of the rice production centers in Banggai Regency. Currently, the problem faced in the production of paddy rice (Oryza sativa L.) is the decline in paddy rice productivity which is influenced by the decline in land fertility.The purpose of this study was to determine the status of soil fertility and the quality of irrigated rice fields in Taugi Village, Masama District. This study took place from October 2023 to January 2024. The methods used were C-organic with the walkley & black method, P2O5 olsen method, K2O, KTK and KB (me / 100 g) and pH PUTS method (rice field soil test kit). soil samples for composites and put in plastic bags for analysis in the Chemistry and Soil Fertility Laboratory. The results of the laboratory analysis will be tabulated in the form of a table to determine the status of soil fertility and the criteria for the suitability of rice fields. The results of the study showed that the soil fertility status of rice fields in Taugi Village, Masama District at points (1,2,3,4 and 5) had a low status which was influenced by the content of KB, N, K2O, C-organic and low soil pH. Therefore, it is necessary to add organic materials and fertilizers containing Nitrogen (N) to improve the fertility status of the soil. Furthermore, the suitability of rice fields in Taugi Village, Masama District is classified as Quite Suitable, it is necessary to make improvements such as adding organic materials and liming, so that a potential rice field land suitability class is obtained.